Fokalizacija v lirskem diskurzu - Balžalorsky Antić, Varja (Primerjalna književnost, 2020)
Until recently, focalization has been a neglected topic in the theory of the lyric. The apparent lack of research interest results from the fact that the lyric was traditionally understood as a fundamentally monologic discourse. In the last two decades, cross-genre narratological studies of poetry began to include focalization as their subject of research (Hühn, Kiefer and Schönert, Rodriguez). Nevertheless, the concept remains theoretically and analytically poorly discussed. In my paper, I attempt to widen the conclusions proposed by these researchers. A fruitful start of the investigation is the application of referential contributions by classical narratologists to the category of the lyric. Recent approaches, especially cognitive ones, should also be taken into account. Jahn's reconceptualization in terms of "windows of focalization" and "screen" as well as Herman's understanding of focalization as specific models of world understanding and epistemic modalities seem important arguments for broadening the concept of focalization in the study of the lyric discourse. After proposing a definition based on the authors mentioned above, I discuss potential objections that could be raised by analysts, interprets, and readers when thinking about focalization in the lyric. Short analyses of poems allow me to define levels where focalization potentially takes place. The paper concludes with an established basic taxonomy for the focalization types of the lyric, citing examples from World and Slovenian poetry, and suggests some topics for further investigation.
Keywords: focalization; fokalizacija; lirski diskurz; lirski subjekt; lyrical discourse; lyrical subject; perspective; perspektiva; poetry; poezija; postclassical narratology; postklasična naratologija; teorija lirike; theory of the lyric; transnaratologija; transnarratology